Extreme Sea-Surface Cooling Induced by Eddy Heat Advection During Tropical Cyclone in the North Western Pacific Ocean - Qiu, Chunhua; Liang, Hong; Sun, Xiujun; Mao, Huabin; Wang, Dongxiao; Yi, Zhenhui; Wirasatriya, Anindya (Frontiers in Marine Science, 2021)
A tropical cyclone (TC) usually induces strong sea surface cooling due to vertical mixing. In turn, surface cooling influences the intensities and tracks of TCs. Therefore, relationship between sea surface temperature and TC is one of important component of air-sea interaction. Sea surface cooling associated with three TCs (Bailu, Lingling, Mitag) was investigated based on wave glider observations, satellite altimetry, and Massachusetts Institute of Technology General Circulation Model (MITgcm) numerical experiments from August 3rd to October 10th, 2019. Surface cooling varied among the three TCs. TC Lingling had the nearest distance to the wave glider position, slowest translation speed and strongest intensity of three TCs, but extreme cooling (1.4 °C) occurred during TC Bailu. Although MITgcm underestimated the extreme cooling, the sea surface temperature (SST) trend driven by the net heat flux, advection and vertical mixing within the mixed layer was greater during TC Bailu than during other TCs. Advection was the largest of the three heat balance terms during TC Bailu, while it was quite small during the other two TCs. Interestingly, the extreme cooling occurred at the position of preexist warm eddy. Based on heat balance analysis, we found that the eddy-induced heat advection transport reached -0.4 °C/day, contributing 60% of the heat balance; this was attributed to extreme cooling via eddy disturbance. We suggest TC Bailu leads to the decrease in SST and increase in area of the cold eddy, and then the cooled-enlarged eddy is advected to the neighbored position of wave glider, which observes the extreme cooling. These findings provide the utilization of wave-glider and are helpful for improving air-sea coupled models during TCs.